2020
DOI: 10.1111/jocd.13606
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor (VDR) gene polymorphism in Egyptian vitiligo patients

Abstract: Vitiligo is considered the most common disorder of pigmentation. Its prevalence ranges between 0.1% and 2% worldwide. The pathogenesis is mainly as a result of affection of the skin melanocytes. Factors as age, race, sex, ethnicity, or skin color do not relate to the incidence of this disease. 1 Vitiligo is categorized as autoimmune, and this is currently the most widely accepted hypothesis. However,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(31 reference statements)
2
6
0
Order By: Relevance
“…In our study, we found that the female sex (57.5%) was more affected than males (42.5%). This is in accordance with the finding of Martins et al (16) and Saudi et al (13) who found that the incidence of vitiligo was higher among female sex. This may be attributed to the fact that females are more concerned by the disease and its distressing appearance more than males, leading to an increased and earlier presentation of females to dermatology clinics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found that the female sex (57.5%) was more affected than males (42.5%). This is in accordance with the finding of Martins et al (16) and Saudi et al (13) who found that the incidence of vitiligo was higher among female sex. This may be attributed to the fact that females are more concerned by the disease and its distressing appearance more than males, leading to an increased and earlier presentation of females to dermatology clinics.…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of the case group was 30.8 years, and 28.11 years in Nejad et al (11) and Amer et al (12) studies respectively. However, in Saudi et al (13) study, mean age of patients was 43.53 ± 14.35 years. These data reinforced that vitiligo is a disease that occurs at any age.…”
Section: Discussionmentioning
confidence: 89%
“…The varied characteristics of the population are also important factors that alter the production of vitamin D at the skin level, among them are age, due to the deterioration of the skin over time, so that older adults have thinner skin, which reduces the ability to synthesize vitamin D, also influences the way of dressing, the place of work, quality of life and the different measures used over the years to limit sun exposure generally have a great impact on the synthesis of vitamin D [6].…”
Section: Table 1 Vitamin D Requirement Per Daymentioning
confidence: 99%
“…Two of the 15 studies were eliminated because they lacked VDR polymorphism data or because they were reviews. The meta-analysis included 13 trials with 2034 cases and 2771 controls [11][12][13][14][15][16][17][18][19][20][21][22][23] (Table 1; Figure 1). Eleven studies examined the VDR ApaI polymorphism, 12 examined the VDR TaqI polymorphism, seven looked at the BsmI polymorphism, and eight looked at the VDR FokI polymorphism (Table 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Some studies have established a correlation between the VDR polymorphisms and vitiligo susceptibility, whereas others have found no correlation. [11][12][13][14][15][16][17][18][19][20][21][22][23] These disparities are likely due to the small sample sizes, low statistical power, and/or clinical heterogeneity. To overcome the limitations of individual studies, resolve discrepancies, and reduce the likelihood of random errors being responsible for false-positive or falsenegative associations, [24][25][26] we conducted an updated meta-analysis to identify whether VDR ApaI, TaqI, BsmI, and TaqI polymorphisms are correlated to vitiligo susceptibility.…”
Section: Introductionmentioning
confidence: 99%